(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The Ghanaian society is highly patriarchal and one of the immediate outcomes is that assignment of roles and responsibilities are typically based on gender lines. This paper is about gender representation in social studies textbooks in Ghana for Junior High School (JHS) students. In this article we argue that this inherent division of responsibilities based on gender navigates into history textbook narratives and influences the roles that are assigned to male and female characters. We further argue that male characters are assigned more superior roles than female characters in Ghanaian history textbooks, albeit subtly. The article uses the Ghanaian social studies textbook for JHS which documents historical accounts of Ghanaian men and women in precolonial, colonial and postcolonial periods. Both content and thematic analyses were used to present evidence for the findings. The contents of the selected textbooks sections were organised into two types of narratives to establish how gender is represented and whether one gender is systematically undermined in the texts. This helped to summarise the content into themes. Firstly, we assessed the representation of male and female characters in the texts to ascertain the extent to which females and males are represented in the narratives. Secondly, we assessed the language used in the textbooks to show if the language and specific key words used favoured particular gender groups. In this article we conclude that linking men to more prestigious occupations and heroic undertakings of the past and silencing of women in such positions, is subtle but predominant in the treatment of history in Ghanaian JHS social studies textbooks. Consequently, we recommend the development of a gender-sensitive policy to mainstream gender neutrality in curriculum development and textbooks contents.